How Could Information Systems Support Transparency to Face Corruption? Systematic Mapping of the Literature - Classe, Tadeu Moreira de; Sousa, Henrique Prado de Sá; Castro, Ronney Moreira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Corruption is a problem that follows the evolution of humanity, taking root in human society and causing global problems in the form of social inequality, the precariousness of public services, and the exhaustion of democracy. In this scenario, transparency is a necessary action against corruption by providing more precise and complete information so that society can understand and supervise government actions. Public access to those information places Information Systems (ISs) at the center of transparency proposals as tools that can help fight against corruption. Problem: Nevertheless, understanding, designing, and deploying ISs with such a purpose is a challenge because they need distinct features. Solution: Therefore, in this paper, we explored research that helps to understand how ISs could help to face corruption considering transparency aspects, such as features, technologies, and application contexts. Method: We described and used a systematic mapping of the literature (SML) for that. Summary Results: In the search step, we found 124 primary studies but, after evaluation criteria, we accepted only 14 of them as relevant to the research. The results point to potential technologies and features that can make up these ISs, such as data openness and privacy, information traceability, data availability, real-time data, and accountability. Contributions to IS: Thus, this study brings contributions to the SI area by identifying aspects to the project of ISs focused on fighting against corruption by supporting information transparency. In addition, beyond the social relevance of this theme, the research is aligned to the GranDSI-BR 2016-2026.